2019
DOI: 10.1039/c8bm01444b
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in nanostructured contrast media development for in vivo photoacoustic imaging

Abstract: To overcome the endogenous photoacoustic contrast arising from endogenous species, specific contrast agents need to be developed, allowing PAI to successfully identify targeted contrast in the range of wavelength in which the interference from the biomatrix is minimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 234 publications
(129 reference statements)
0
34
0
Order By: Relevance
“…ICG is one of the few photoacoustic and fluorescent contrast agents approved for intraoperative clinical use by the US FDA, and available clinical and experimental results have shown that ICG-based PAI can play an important role in intraoperative tumor number and boundary determination and postoperative assessments. 29,30 Because ICG is nontargeting and has a high affinity for plasma protein, it has good application prospects as a blood flow monitoring agent and can provide good oncologic imaging results. 31 If ICG exists in the form of free molecules, problems such as poor water stability and rapid clearance from the body may arise, thus reducing its imaging time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICG is one of the few photoacoustic and fluorescent contrast agents approved for intraoperative clinical use by the US FDA, and available clinical and experimental results have shown that ICG-based PAI can play an important role in intraoperative tumor number and boundary determination and postoperative assessments. 29,30 Because ICG is nontargeting and has a high affinity for plasma protein, it has good application prospects as a blood flow monitoring agent and can provide good oncologic imaging results. 31 If ICG exists in the form of free molecules, problems such as poor water stability and rapid clearance from the body may arise, thus reducing its imaging time.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with ultrasound, PAI provides intuitive and clear tissue contrast images with high sensitivity, which is conducive to accurate diagnosis and localization of tumors. 29,30 Fluorescence imaging has the advantages of high sensitivity and intuitive image, but there are some shortcomings such as low spatial resolution and poor tissue permeability, and the localization of the lesion is inferior to that of ultrasound and photoacoustic. The multimodal imaging formed by the combination of photoacoustic, ultrasound and fluorescence imaging can directly and comprehensively obtain the tumor tissue structure and the molecular information of cell, which is conducive to the accurate early diagnosis, localization of tumors, and the visual evaluation of tumor areas after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…12 It utilizes photothermal agents (PTAs) to convert light energy into heat energy, leading to elevated temperatures at the tumor sites to kill the tumor cells. Because NIR light has a better tissue penetration ability, 464 the ideal PTA should have high absorption in the NIR region. The remarkable feature of inorganic PTAs, 11,465 e.g., gold nanorods, platinum quantum dots, and graphene nanosheets, is their ability to absorb and manipulate light at the subwavelength scale by supporting coherent electronic oscillation, which is called localized surface plasmon resonance (LSPR).…”
Section: Principle Of Chemotherapeutic Drug Deliverymentioning
confidence: 99%
“…PA is an emerging biomedical imaging technique based on the transition from absorbed photons to acoustic waves which are then detected and processed to form an image. [27] In our system, IR780, a superb PA contrast agent, was used to visualize the tumor morphology in vivo. As shown in Figure 6D, after intravenous injection of PBS, the tumor barely exhibited PA signal.…”
Section: Tumor-targeted Imaging Of Ir780-pdmsmentioning
confidence: 99%